Srub suits vs clean air suits: a thermal properties comparison - Abreu, Isabel (2014)
In operationg room (OR), the health professionals are exposed to stress situations that can influence their physical and psychological performance. The thermal properties are an important requirement for the best performance of OR medical clothing, that plays a crucial role in thermal comfort of the user, that involve the regulation of heat and mass transfer between a clothed body and the environment. In this way, the aim of this work was comparison of thermal properties between scrub and clean air suits. The test was performed on a thermal manikin and Alambeta to measure clothing insulation and to evaluate the thermal comfort. These tests provide a good estimate of the total dry heat loss from the body and the distribution of heat flow between body surface and textile materials.